1994
DOI: 10.1111/j.1365-2710.1994.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related admissions to an Australian hospital

Abstract: This study was conducted to determine the prevalence of drug-related hospital admissions in southern Tasmania, Australia. The causes of consecutive admissions to medical wards of the Royal Hobart Hospital were reviewed. Comprehensive data were collected over a 10-week period on 691 admissions (median age: 67 years and range: 11-97 years; 50.8% males). Sixty-eight (9.8%) of the admissions were classified as being either probably or definitely drug-related. Most of these admissions were attributable to intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 19 publications
1
33
0
3
Order By: Relevance
“…However, the patterns of drug prescribing are often inappropriate. [2,3] General practice database has been used as an effective method for pharmacoepidemiologic research. [4] Until 1990s, prescribers had two classes of drug to control hyperglycaemia (insulin and sulfonylurea).…”
Section: Introductionmentioning
confidence: 99%
“…However, the patterns of drug prescribing are often inappropriate. [2,3] General practice database has been used as an effective method for pharmacoepidemiologic research. [4] Until 1990s, prescribers had two classes of drug to control hyperglycaemia (insulin and sulfonylurea).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been established that elderly patients use more medicaments than younger age groups (LANDAHL 1987;WILLIAMS and LOWENTHAL 1992;SLOAN 1992;STEWART and COOPER 1994) and thus have a greater risk of drug-drug interactions occurring (KELLAWAY and MCCRAE 1973;LAWSON and JICK 1976;LEVY et al 1980;WILLIAMSON and CHOPIN 1980;SIMONS et al 1992;SCHENKER and BAY 1994;STANTON et al 1994;STEWART and COOPER 1994) (Fig. 1).…”
Section: B Agementioning
confidence: 99%
“…It was found that 40% of patients taking quinidine were also taking a digitalis glycoside, and nearly one-third of patients taking warfarin were also taking a drug with an interacting potential. STANTON et al (1994) studied drug-related admissions to an Australian hospital. The sample size of the study was 463 patients, of whom 332 attended the medical clinic and 131 attended the geriatric clinic.…”
Section: Inappropriate Unnecessary and Interacting Medicationmentioning
confidence: 99%
“…6,7 The elderly populations are at increased risk because of decreased functioning of the systems, more number of medications due to comorbidities, and complicated drug regimens. 8,9 When two drugs are concomitantly administered through oral route, the dissolution pattern of one drug may affect the dissolution of the other. During poly pharmacy there may be increased or decreased acidity in gastric environment and hence degree of ionization of one drug in the presence of other in stomach pH may get altered which affects the disintegration and dissolution of tablet dosage forms.…”
Section: Introductionmentioning
confidence: 99%